Farmers' Perception of the Usefulness of Available Infrastructural Facilities in the Rural Areas of Oyo State - A O Akinsorotan (Journal of Agricultural Extension, 2007)
The study investigated rural farmers' perception of the usefulness of available infrastructural facilities in their communities, using 120 randomly selected farmers in Oyo State, Nigeria. It examined availability, functioning status, sources of provision, utilization, relevance and general usefulness of selected infrastructural facilities. Results showed that rural farmers perceived infrastructural facilities provided as very relevant and useful to their needs. The higher the farmer's farm size, the higher the rating of the usefulness of available infrastructural facilities. The results furthershowed that totalfarm size wasbetweenlowandmediumandcontact with extension agent was low. Finally, the study revealed that the current working condition of the available infrastructural facilities calls for urgent improvement and adequate monitoring and supervision.